1968
DOI: 10.1161/01.res.23.6.753
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode Study of Delayed Conduction in the Canine Right Bundle Branch

Abstract: The electrophysiology of conduction delay was investigated in the semiisolated right bundle branch of 30 large mongrel dogs. Delay was produced by the external application of an electric blocking current to the bundle branch. Multiple recordings with glass capillary microelectrodes revealed two basic deflections associated with the delay phenomenon. An initial, or leading, deflection originated from the proximal or leading edge of the block and was rapidly transmitted through the block with progressive decay o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1971
1971
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The increase in A Vnodal transmission time with shortening of cycle length was due to "stagnation" between N and NH zone. This stagnation was likened to the mechanism of electrotonic transmission described for other cardiac tissues, where an inexcitable segment, interposed between two excitable regions, functions as a purely passive resistance-capacitance circuit (12,37,67,200). The stagnation is caused by cessation of active transmission at the inexcitable element, which can be crossed by electrotonic current bringing distal excitable ceUs to threshold.…”
Section: A Decremental Conduction Versus Electrotonic Transmissionmentioning
confidence: 72%
“…The increase in A Vnodal transmission time with shortening of cycle length was due to "stagnation" between N and NH zone. This stagnation was likened to the mechanism of electrotonic transmission described for other cardiac tissues, where an inexcitable segment, interposed between two excitable regions, functions as a purely passive resistance-capacitance circuit (12,37,67,200). The stagnation is caused by cessation of active transmission at the inexcitable element, which can be crossed by electrotonic current bringing distal excitable ceUs to threshold.…”
Section: A Decremental Conduction Versus Electrotonic Transmissionmentioning
confidence: 72%
“…The majority of knowledge about cellular electrical events accompanying cardiac ischemia is derived from experimental models in which the tissue was uniformly exposed to ischemic components throughout its length (Downar et al, 1977;Wennemark et al, 1968;Pappano, 1970;Carmeliet and Vereecke, 1969;Trautwein and Schmidt, I960;Engstfeld et al, 1961). A series of very interesting studies by Cranefield et al reported the development of a remarkable model for the abnormal conduction which might exist in clinical arrhythmias associated with myocardial infarction Cranefield et al, 1972).…”
mentioning
confidence: 99%
“…Accepted for publication November 24, 1970. been demonstrated by recording mechanical activity in strips of turtle heart depressed with high external K + (8,9); Drury (10) showed slow conduction in atrial muscle, depressed by cold or by pressure, by recording electrograms in normal and depressed tissue. Most studies of conduction in depressed cardiac fibers using single cell recording of transmembrane action potentials (11)(12)(13)(14)(15)(16) have been carried out on tissue uniformly depressed throughout its length.…”
mentioning
confidence: 99%